Greek Education in the Republic of South Africa - Krystallidis, Anastasia (Études helléniques / Hellenic Studies, 2005)
This article consists of two components. The first, based on the study Greek Education in the Republic of South Africa, was expounded upon by the South African working team and published by the University of Créte-EDIAMME, in 2003. The second component is a study of the SAHETI School based on the personal experiences and association of the author with the school, as a teacher of Greek from 1975 on and as principal for the past ten years.